(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Retail banking services are one of the most attractive and highly profitable areas of activity of commercial banks. Therefore, despite the difficulties in the banking sector, credit institutions are paying special attention to the development of this segment and are consistently expanding the range of services provided to individuals. As one of the main areas of retail activity of commercial banks, the provision of deposit, loan and settlement and cash services to individuals occupies an important place. Along with these operations, banks also offer customers various additional financial services, including money transfers, bank cards, investment and advisory services. This serves to diversify the activities of banks in the retail segment, comprehensively meet the needs of customers and increase profitability